The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025933
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Fused Deposition Modeling by Controlling Extruder Height and Extrusion Amount

Abstract: Fused deposition modeling (FDM) 3D printers form objects by stacking layers having a linear structure. To print fine structures, an appropriate choice of parameters is necessary, or printing error occurs. On the other hand, the printing error is exploited as an expression technique. However, the relation between the printed structure and the parameters causing the printing error is unclear. In this paper, we focus on the height position of the extruder and the amount of extruded material, and explore the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Furbrication utilizes the stringing effect of 3D printing filaments to create hairlike structures [13]. Expressive FDM [32] generates new forms by varying parameters that affect the height and amount of extruded material, similar to aesthetic filament sculptures [14] and Making Mistakes [33]. This can also be used to print tactile sheets [31].…”
Section: Leveraging 3d Printing Parameters Of Fdm Printersmentioning
confidence: 99%
“…Furbrication utilizes the stringing effect of 3D printing filaments to create hairlike structures [13]. Expressive FDM [32] generates new forms by varying parameters that affect the height and amount of extruded material, similar to aesthetic filament sculptures [14] and Making Mistakes [33]. This can also be used to print tactile sheets [31].…”
Section: Leveraging 3d Printing Parameters Of Fdm Printersmentioning
confidence: 99%
“…WirePrint allows diagonal z-movements of a delta style printer to construct sparse wireframe meshes so reduce the printing time [22]. Controlling the height of the nozzle as well as the amount of material extrusion, expressive textures such as a fluffy surface can be created [37]. 3D printed fabric is an additional technique enabling the weaving movements of the header, enabling users to create a flexible fabric out of rigid plastic [36].…”
Section: Direct G-code Manipulation To Enhance Fdm Capabilitymentioning
confidence: 99%
“…Two publications in the last 12 months have investigated a new strategy for material extrusion additive manufacturing, in which the speed of the nozzle and the rate of material extrusion were adjusted to achieve new structures [ 61 , 62 ]. Figure 11 shows the strategy used by Yuk and Zhao [ 62 ]: by setting a low extrusion rate relative to nozzle speed, the filament was stretched to be narrower than the nozzle diameter, whereas setting a high extrusion rate caused the filament to either widen or fold on itself (“coiling” or “accumulation” in Fig.…”
Section: Innovative Strategies For Polymer Depositionmentioning
confidence: 99%
“…The authors suggested that innovations and applications of material extrusion additive manufacturing have been severely hampered by the limitations of typical deposition strategies. Takahashi and Miyashita [ 61 ] also undertook a detailed study varying the extrusion rate and height of the nozzle but for polylactide as opposed to a silicone hydrogel. They demonstrated capabilities to print a range of structural geometries with a focus on achieving different surface textures.…”
Section: Innovative Strategies For Polymer Depositionmentioning
confidence: 99%
See 1 more Smart Citation